Quantitative determination of cereulide by LC-MS/MS requires partitioning/salting-out extraction with water/acetonitrile for a reliable measurement in powdered infant formula - Mathieu Dubois; Thomas Bessaire; Xanthippi Theurillat; Christophe Fuerer; Marie-Claude Courtet-Compondu; Bjørn Eriksen; Adrienne Tarres; Rosemarie Jenni; Sabine Lahrichi; Thierry Delatour; Michael Affolter; Marjorie Guitard-Uldry; et al. (International Journal of Food Microbiology, 2026)

An expanded polar record of the Toarcian hyperthermal from Vilyui River Basin (Siberia) - Alicia Fantasia; Thomas Letulle; Mikhail A. Rogov; Alexey P. Ippolitov; Oleg A. Lutikov; Nikolay Zverkov; Arnauld Vinçon-Laugier; Thierry Adatte; Jorge E. Spangenberg; Guillaume Paris; Jeremy E. Martin; Christophe Lécuyer; et al. (Global and Planetary Change, 2026)

Markers for anthropogenic sources of secondary organic aerosol: new evaluation from simulation chamber study - Diana L. Pereira; Aline Gratien; Chiara Giorio; Francesco Battaglia; Emmanuelle Mebold; Thomas Bertin; Mathieu Cazaunau; Edouard Pangui; Antonin Berge; Cécile Gaimoz; Bénédicte Picquet-Varrault; Jean-François Doussin; et al. (Atmospheric Environment, 2026)

Understanding forest transitions and lock-ins in Latin American agro-forest frontiers: aligning theory to practice for accelerating restoration - Madelon Lohbeck; Thomas W. Kuyper; Frans Bongers; Rocío Aguilar-Fernández; Patricia Balvanera; Jelle Behagel; Carolina Berget; Felix Bianchi; Irene Maria Cardoso; Lucas de Carvalho Gomes; Juana Cruz-Morales; Mathieu Decuyper; et al. (Global Environmental Change, 2026)

Host Rejection of the White Mustard (Sinapis alba) by a Major Oilseed Rape Pest Is Driven by the Avoidance of Sinalbin - Thomas Giguère; Célia El Marahi; Christophe Lunel; Mathieu Bussy; Léo Andruszkow; Chrystelle Paty; Anne Marie Cortesero; Maxime R. Hervé (Journal of Chemical Ecology, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Robustness of critical soil moisture to curve-fitting methods and its variability with soil depth, soil texture, and climatic conditions: insights from lysimeter data in Germany - Xiao Lu; Jannis Groh; Alexander Graf; Thomas Pütz; Horst H. Gerke; Ralf Gründling; Holger Rupp; Ralf Kiese; Hans Jörg Vogel; Mathieu Javaux; Harry Vereecken; Harrie-Jan Hendricks Franssen (Journal of Hydrology, 2026)

Identifying Post-Stroke Spasticity in Swedish Healthcare Registers: A Real-World Analysis - Susanne Palmcrantz; Alexandros Zampakas; Kjell Kullander; Ann-Charlotte Mårdby; Matilda Ahl; Mathieu Beneteau; Thomas Cars; Jörgen Borg (Toxicon, 2026)

A digital twin integrating multi-objective optimization to support fryer operators in managing potato crisps production - Manon Perrignon; Mathieu Emily; Mélanie Munch; Paul Debuire; Romain Jeantet; Thomas Croguennec (Journal of Food Engineering, 2026)

Spatial distribution of persistent components of particulate matter near a hazardous waste thermal treatment facility - Chuqi Guo; Oluwafeyikemi Ogunmusi; Martine E. Mathieu-Campbell; Myron Lard; Thomas Blanchard; Lavrent Khachatryan; Brenda Vallee; Wilma Subra; Stephania A. Cormier; Slawo Lomnicki; Jennifer Richmond-Bryant (Environmental Pollution, 2026)

Persistent chemicals in particulate matter (PM) near a hazardous waste thermal treatment facility - Chuqi Guo; Martine E. Mathieu-Campbell; Thomas Blanchard; Lavrent Khachatryan; Md Abdullah Al-Mamun; Qingzhao Yu; Myron Lard; Oluwafeyikemi Ogunmusi; Brenda Vallee; Wilma Subra; Iriel Edwards; David Malone; et al. (Atmospheric Pollution Research, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Synergistic four physical phenomena in a 3D photocatalyst for unprecedented overall water splitting - Laroussi Chaabane; Ivalina Trendafilova; Thomas Lourdu Madanu; Maxime Mathieu; Mehdi Feizpour; Marwa Chaaben; Safa Chaaben; Jun Chen; Heidi Ottevaere; Bao-Lian Su (Chemical Engineering Journal, 2026)

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Immune cell-resolved transcriptomics provides insights into the basis for variations of fish genetic resistance to viral disease - Thomas C. Clark; Valentin Thomas; Richard S. Taylor; Mathieu Charles; Audrey Laurent; Isabelle Schwartz-Cornil; Bertrand Collet; Delphine Lallias; Daniel J. Macqueen; Samuel A.M. Martin; Pierre Boudinot (Fish & Shellfish Immunology, 2025)

Chemical constituents from the roots of Berberis aetnensis C. Presl. and their chemotaxonomic significance - Thomas Maroselli; Ange Bighelli; Joseph Casanova; Mathieu Paoli (Biochemical Systematics and Ecology, 2025)

Understanding the relationship between foraminiferal Mg/Ca and clumped isotope thermometers - Marion Peral; Thibaut Caley; Bruno Malaizé; Thomas Extier; Linda Rossignol; Héloïse Barathieu; Émilie Dassié; Franck Bassinot; Dominique Blamart; Mathieu Daëron (Geochimica et Cosmochimica Acta, 2025)

Comparison of high-fidelity transport code predictions against the NECTAR intra-pin reaction rate measurements - Tom Mager; Mathieu Hursin; Kyle Vaughn; Sooyoung Choi; Brendan Kochunas; Thomas Ligonnet; Vincent Lamirand; Oskari Pakari; Carlo Fiorina; Andreas Pautz (Annals of Nuclear Energy, 2025)

Use of commercial serological tests to detect schistosomiasis in sheep - Manon Blin; Félix Bornier; Nathalie Lazzarin; Justine Alonzi; Bruno Polack; Isabelle Vallée; Anne Rognon; Eglantine Mathieu-Bégné; Myriam Thomas; Denis Limonne; Jérôme Boissier (Veterinary Parasitology, 2025)

Spatial biases in oxygen-based Phanerozoic seawater temperature reconstructions - Alexandre POHL; Thomas W. WONG HEARING; Arnaud BRAYARD; Ethan GROSSMAN; Michael M. JOACHIMSKI; Guillaume LE HIR; Thomas LETULLE; Daniel J. LUNT; Mathieu MARTINEZ; Emmanuelle PUCEAT; Guillaume SUAN; Paul VALDES; et al. (Earth and Planetary Science Letters, 2025)

Understanding physiological mechanisms of European beech dieback responses to climate using a triple isotope approach in northern Switzerland - Anna Neycken; Marco M. Lehmann; Matthias Saurer; Thomas Wohlgemuth; Esther R. Frei; Mathieu Lévesque (Dendrochronologia, 2025)

Combining acoustic telemetry with archival tagging to investigate the spatial dynamic of the understudied pollack, Pollachius pollachius - Marine Gonse; Martial Laurans; Justus Magin; Tina Odaka; Jean‐Marc Delouis; Stéphane Martin; François Garren; Coline Lazard; Mickael Drogou; Thomas Stamp; Peter Davies; Alice Hall; et al. (Journal of Fish Biology, 2025)
Combining fish tracking methods is a promising way of leveraging the strengths of each approach while mitigating their individual weaknesses. Acoustic telemetry provides presence information as the fish move within receiver range, eliminating the need for tag recovery. Archival tags, on the other hand, record environmental variables on tag retrieval, enabling continuous path reconstruction of a fish beyond coastal regions. This study capitalizes on the combination of both methods for geolocating pollack, Pollachius pollachius , an understudied species of the northeast Atlantic, where declining stocks are raising concern. Essential knowledge of population structure and connectivity between essential habitats is critically lacking and could help inform stock assessment and management. The aims of the study were (1) to evaluate the feasibility of double‐tagging pollack, known for being challenging to tag, and (2) to track seasonal movements across the Channel to gain first insights into pollack spatial ecology. In 2022, an extensive network of acoustic receivers was been deployed in the Channel along the French, English, and Belgian coasts as part of the Fish Intel project. We tagged 83 pollack with acoustic transmitters, among which 48 were double‐tagged with data storage tags. Post‐tagging survival assessment, conducted on a subset of 35 individuals, revealed a successful procedure with a 97% short‐term survival rate. By October 2023, the acoustic telemetry network detected 30 out of 83 pollack at least once, with no large‐scale movements observed across the Channel. Presence in the network fluctuates seasonally, peaking in summer, particularly among immature fish. Integrating acoustic detections with temperature and depth time series in a geolocation model enabled trajectory reconstruction of 10 recaptured pollack, seven of which were detected by the network. This combined tracking approach revealed coastal movements along the coast of Brittany in France, highlighting the ecological significance of the Iroise Sea for pollack throughout the year, particularly in summer. The geolocation model also suggested movements towards the entrance of the western Channel. This study highlights the complementarity of acoustic telemetry and archival tagging in reconstructing fish movements in their natural environment. As data accumulate, these innovative tracking methods promise to continually unveil new insights into the spatial ecology of the understudied pollack, which is essential for the species' management.

Machine learning for predicting industrial performance: Example of the dry matter content of emmental-type cheese - Manon Perrignon; Mathieu Emily; Mélanie Munch; Romain Jeantet; Thomas Croguennec (International Dairy Journal, 2025)

Effects of home-based exercise with or without cognitive training on cognition and mobility in cardiac patients: A randomized clinical trial - Florent Besnier; Emma Gabrielle Dupuy; Christine Gagnon; Thomas Vincent; Tudor Vrinceanu; Caroll-Ann Blanchette; Josep Iglesies-Grau; Kathia Saillant; Malorie Chabot-Blanchet; Sylvie Belleville; Martin Juneau; Paolo Vitali; et al. (GeroScience, 2025)

CORTEX experiments – Part I: Modulation campaigns in AKR-2 & CROCUS for the validation of neutron noise codes - Vincent Lamirand; Alexander Knospe; Klemen Ambrožič; Sebastian Hübner; Carsten Lange; Oskari Pakari; Fanny Vitullo; Adolfo Rais; Joachim Pohlus; Uwe Paquee; Christoph Pohl; Nicolas Weiss; et al. (Annals of Nuclear Energy, 2025)

Technosols made of urban wastes are suitable habitats for flora and soil macrofauna - Charlotte Pruvost; Jérôme Mathieu; Jeanne Vallet; Florence Dubs; Agnès Gigon; Thomas Lerch; Manuel Blouin (Ecological Engineering, 2025)

Traction modifies the contact area and the vertical and horizontal stress distributions beneath the tyre - Loraine ten Damme; Alvaro Calleja-Huerta; Lars Juhl Munkholm; Per Schjønning; Thomas Keller; Mathieu Lamandé (Soil and Tillage Research, 2024)

The interplay of local adaptation and gene flow may lead to the formation of supergenes - Paul Jay; Thomas G. Aubier; Mathieu Joron (Molecular Ecology, 2024)
Supergenes are genetic architectures resulting in the segregation of alternative combinations of alleles underlying complex phenotypes. The co‐segregation of alleles at linked loci is often facilitated by polymorphic chromosomal rearrangements suppressing recombination locally. Supergenes are involved in many complex polymorphisms, including sexual, colour or behavioural polymorphisms in numerous plants, fungi, mammals, fish, and insects. Despite a long history of empirical and theoretical research, the formation of supergenes remains poorly understood. Here, using a two‐island population genetic model, we explore how gene flow and the evolution of overdominant chromosomal inversions may jointly lead to the formation of supergenes. We show that the evolution of inversions in differentiated populations, both under disruptive selection, leads to an increase in frequency of poorly adapted, immigrant haplotypes. Indeed, rare allelic combinations, such as immigrant haplotypes, are more frequently reshuffled by recombination than common allelic combinations, and therefore benefit from the recombination suppression generated by inversions. When an inversion capturing a locally adapted haplotype spreads but is associated with a fitness cost hampering its fixation (e.g. a recessive mutation load), the maintenance of a non‐inverted haplotype in the population is enhanced; under certain conditions, the immigrant haplotype persists alongside the inverted local haplotype, while the standard local haplotype disappears. This establishes a stable, local polymorphism with two non‐recombining haplotypes encoding alternative adaptive strategies, that is, a supergene. These results bring new light to the importance of local adaptation, overdominance, and gene flow in the formation of supergenes and inversion polymorphisms in general.

Acoustic telemetry suggests the lesser spotted dogfish Scyliorhinus canicula stays and uses habitats within a French offshore wind farm - Pierre Labourgade; Lydie I.E. Couturier; Jérôme Bourjea; Mathieu Woillez; Eric Feunteun; Jan T. Reubens; Thomas Trancart (Marine Environmental Research, 2024)

Reconstruction and verification of mechanism and triggering conditions of the Hermitage landslide at the Vaches Noires cliffs (Normandy) - Mohamed Kouah; Yannick Thiery; Olivier Maquaire; François Nicot; Antoine Wautier; Thomas Roulland; Guillaume Thirard; Mathieu Fressard; Stéphane Costa; Robert Davidson (Geomorphology, 2024)

The multi-objective data-driven approach: A route to drive performance optimization in the food industry - Manon Perrignon; Thomas Croguennec; Romain Jeantet; Mathieu Emily (Trends in Food Science & Technology, 2024)

Enhancing endurance performance with combined imagined and actual physical practice - Robin Souron; Benjamin Pageaux; Nathan Grosboillot; Aymeric Guillot; Mathieu Gruet; Mathilde F. Bertrand; Guillaume Y. Millet; Thomas Lapole (European Journal of Applied Physiology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Pottery use across the Neolithic transition in northern Belgium: evidence from isotopic, molecular and microscopic analysis - Dimitri Teetaert; Marieke Vannoorenberghe; Thomas Van de Velde; Mathieu Boudin; Samuel Bodé; Lucy Kubiak-Martens; Mathijs Baert; Frederic Lynen; Philippe Crombé; Pascal Boeckx (Archaeological and Anthropological Sciences, 2024)
This study represents the first extensive residue analysis of prehistoric pottery from northern Belgium. It examines pottery use and culinary practices across the Mesolithic-Neolithic transition, from the late 6th to the early 4th millennium cal BC. Residue analyses were performed on more than 200 samples from nine archaeological sites, representing different cultural groups from this transitional phase. This includes the analysis of charred food residues encrusted on the vessel surfaces by elemental analysis-isotope ratio mass spectrometry (EA-IRMS), gas chromatography-mass spectrometry (GC-MS), stereomicroscopic analysis and Scanning Electron Microscopy (SEM), as well as the analysis of absorbed lipids by gas chromatography-combustion-isotope ratio mass spectrometry (GC-C-IRMS). This study provides the first evidence of ruminant dairy fats in Early Neolithic Limburg pottery, supporting the hypothesis that this pottery was produced and used by LBK farmers rather than hunter-gatherer populations. The first indigenous pottery of the Swifterbant culture was frequently used to process freshwater fish (often together with plant foods) and ruminant meat, although several of the studied vessels likely contained mixtures of resources which could also include porcine products. Ruminant dairy is nearly absent from this pottery. Similar results were obtained for pottery of the subsequent Michelsberg culture/Group of Spiere of the late 5th and early 4th millennium cal BC. The limited presence of ruminant dairy fats in this pottery contrasts with the findings for Middle Neolithic pottery from neighbouring regions, providing further evidence for the existence of regional variations in pottery use or culinary practices throughout prehistoric NW Europe. However, our current view of pottery use during the Mesolithic-Neolithic transition in northern Belgium might be biased by the difficulties in distinguishing between wild and domesticated ruminant adipose fats as well as in detecting plant foods through lipid residue analysis.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Accessible methods and tools to estimate chemical exposure in humans to support risk assessment: A systematic scoping review - Maria E. Kalyva; Gunn E. Vist; Michael Guy Diemar; Graciela López-Soop; T.J. Bozada; Thomas Luechtefeld; Erwin L. Roggen; Hubert Dirven; Mathieu Vinken; Trine Husøy (Environmental Pollution, 2024)

Comparison of supervised classifications to discriminate seaweed-dominated habitats through hyperspectral imaging data - Wendy Diruit; Thomas Burel; Touria Bajjouk; Anthony Le Bris; Sophie Richier; Sara Terrin; Mathieu Helias; Valérie Stiger-Pouvreau; Erwan Ar Gall (Journal of Applied Phycology, 2024)

Slower growth prior to the 2018 drought and a high growth sensitivity to previous year summer conditions predisposed European beech to crown dieback - Anna Neycken; Thomas Wohlgemuth; Esther R. Frei; Stefan Klesse; Andri Baltensweiler; Mathieu Lévesque (Science of The Total Environment, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

HBM4EU chromates study – PFAS exposure in electroplaters and bystanders - Thomas Göen; Annalisa Abballe; Radia Bousoumah; Lode Godderis; Ivo Iavicoli; Anna Maria Ingelido; Veruscka Leso; Johannes Müller; Sophie Ndaw; Simo P. Porras; Jelle Verdonck; Tiina Santonen; et al. (Chemosphere, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Snow cover persistence as a useful predictor of alpine plant distributions - Thomas Panchard; Olivier Broennimann; Mathieu Gravey; Grégoire Mariethoz; Antoine Guisan (Journal of Biogeography, 2023)
Aim Snow cover persistence (SCP) has significant effects on plants in high‐elevation ecosystems. It determines the length of the growing season, provides insulation against low temperatures and influences water availability, thereby shaping the vegetation mosaic. Despite its importance, SCP is rarely used in plant species distribution modelling. In this study, we examine whether incorporating SCP in plant species distribution models (SDMs) improves their predictive power. We investigate the link between species' ecology and SDM improvements by the addition of various SCP predictors. Location Western Swiss Alps. Taxon 206 alpine flowering plants (angiosperms). Methods We produced three maps of landsat satellite‐based SCP indices over an entire mountain region, one of them using an online open access platform allowing quick and easy replication and used them as a predictor in plant SDMs alongside commonly used predictors. We tested whether this improved the predictive performance of plant SDMs. Results All three SCP indices improved the overall SDM predictive accuracy, but the overall improvement was potentially limited by their correlation with other climatic predictors. Alpine plant species known for their dependence on snow benefited more from the additional snow information. Main Conclusions SCP should be used for predicting at least the distribution of alpine, snow‐related plant species. Given that adding snow cover improves SDMs and that snow duration decreases as climate warms, future predictions of alpine plant distributions should account for both snow predictor and associated snow change scenarios.

A Meta-analysis of Soil Susceptibility to Machinery-Induced Compaction in Forest Ecosystems Across Global Climatic Zones - Meisam Nazari; Emmanuel Arthur; Mathieu Lamandé; Thomas Keller; Nataliya Bilyera; Samuel Bickel (Current Forestry Reports, 2023)

Trophic interactions between native newts and introduced mosquitofish suggest invaded ponds may act as demographic sinks - Benjamin Lejeune; Vincent Clément; Thomas Nothomb; Gilles Lepoint; Mathieu Denoël (Biological Invasions, 2023)

InSpectra – A platform for identifying emerging chemical threats - Mathieu Feraud; Jake W. O’Brien; Saer Samanipour; Pradeep Dewapriya; Denice van Herwerden; Sarit Kaserzon; Ian Wood; Cassandra Rauert; Kevin V. Thomas (Journal of Hazardous Materials, 2023)

Consensus Recommendations for Clinical Outcome Assessments and Registry Development in Ataxias: Ataxia Global Initiative (AGI) Working Group Expert Guidance - Thomas Klockgether; Matthis Synofzik; Saud Alhusaini; Mathieu Anheim; Irina Antonijevic; Tee Ashizawa; Luis Bataller; Mélanie Berard; Enrico Bertini; Sylvia Boesch; Pedro Braga-Neto; Emanuel Cassou; et al. (The Cerebellum, 2023)
To accelerate and facilitate clinical trials, the Ataxia Global Initiative (AGI) was established as a worldwide research platform for trial readiness in ataxias. One of AGI’s major goals is the harmonization and standardization of outcome assessments. Clinical outcome assessments (COAs) that describe or reflect how a patient feels or functions are indispensable for clinical trials, but similarly important for observational studies and in routine patient care. The AGI working group on COAs has defined a set of data including a graded catalog of COAs that are recommended as a standard for future assessment and sharing of clinical data and joint clinical studies. Two datasets were defined: a mandatory dataset (minimal dataset) that can ideally be obtained during a routine clinical consultation and a more demanding extended dataset that is useful for research purposes. In the future, the currently most widely used clinician-reported outcome measure (ClinRO) in ataxia, the scale for the assessment and rating of ataxia (SARA), should be developed into a generally accepted instrument that can be used in upcoming clinical trials. Furthermore, there is an urgent need (i) to obtain more data on ataxia-specific, patient-reported outcome measures (PROs), (ii) to demonstrate and optimize sensitivity to change of many COAs, and (iii) to establish methods and evidence of anchoring change in COAs in patient meaningfulness, e.g., by determining patient-derived minimally meaningful thresholds of change.

A research-action process to implement priority areas for alien plant clearing on Reunion Island - Pauline Fenouillas; Claudine Ah-Peng; Elise Amy; Isabelle Bracco; Laurent Calichiama; Emilie Cazal; Mélodie Gosset; Florent Ingrassia; Christophe Lavergne; Benoit Lequette; Jean-Cyrille Notter; Jean-Marie Pausé; et al. (Biological Invasions, 2023)

Proposal for reference values for the developmental effects of valproate based on human data using a benchmark dose approach - Isabelle Manière-Guerrero; Erminio Bonizzoni; Dina Battino; François Clinard; Aurélie Mathieu-Huart; Emilio Perucca; François Pouzaud; Torbjorn Tomson; Sanjeev V. Thomas; Frank Vajda; Christophe Rousselle (Regulatory Toxicology and Pharmacology, 2023)

Modulation of the crystallization of rapeseed oil using lipases and the impact on ice cream properties - Aurélie Monié; Thomas Habersetzer; Léa Sureau; Annabelle David; Karine Clemens; Myriam Malet-Martino; Emile Perez; Sophie Franceschi; Stéphane Balayssac; Mathieu Delample (Food Research International, 2023)

Maerl-associated macroalgae in the bay of Brest (Brittany, France) - Mathieu Helias; Thomas Burel (Marine Biodiversity, 2023)

Isotopic niche partitioning of co-occurring large marine vertebrates around an Indian ocean tropical oceanic island - Guillaume Chandelier; Jeremy J. Kiszka; Violaine Dulau-Drouot; Claire Jean; Thomas Poirout; Vanessa Estrade; Mathieu Barret; Jacques Fayan; Sébastien Jaquemet (Marine Environmental Research, 2023)

Long-term exposure to nitrogen dioxide air pollution and breast cancer risk: A nested case-control within the French E3N cohort study - Amina Amadou; Delphine Praud; Thomas Coudon; Floriane Deygas; Lény Grassot; Mathieu Dubuis; Elodie Faure; Florian Couvidat; Julien Caudeville; Bertrand Bessagnet; Pietro Salizzoni; Karen Leffondré; et al. (Environmental Pollution, 2023)

Sensitivity analysis of a crop metapopulation model - Baptiste Rouger; Isabelle Goldringer; Pierre Barbillon; Anne Miramon; Abdel Kader Naino Jika; Mathieu Thomas (Ecological Modelling, 2023)

Telomeres, the loop tying cancer to organismal life‐histories - Beata Ujvari; Nynke Raven; Thomas Madsen; Marcel Klaassen; Antoine M. Dujon; Aaron G. Schultz; Leonard Nunney; Jean‐François Lemaître; Mathieu Giraudeau; Frédéric Thomas (Molecular Ecology, 2022)
Recent developments in telomere and cancer evolutionary ecology demonstrate a very complex relationship between the need of tissue repair and controlling the emergence of abnormally proliferating cells. The trade‐off is balanced by natural and sexual selection and mediated via both intrinsic and environmental factors. Here, we explore the effects of telomere‐cancer dynamics on life history traits and strategies as well as on the cumulative effects of genetic and environmental factors. We show that telomere‐cancer dynamics constitute an incredibly complex and multifaceted process. From research to date, it appears that the relationship between telomere length and cancer risk is likely nonlinear with good evidence that both (too) long and (too) short telomeres can be associated with increased cancer risk. The ability and propensity of organisms to respond to the interplay of telomere dynamics and oncogenic processes, depends on the combination of its tissue environments, life history strategies, environmental challenges (i.e., extreme climatic conditions), pressure by predators and pollution, as well as its evolutionary history. Consequently, precise interpretation of telomere‐cancer dynamics requires integrative and multidisciplinary approaches. Finally, incorporating information on telomere dynamics and the expression of tumour suppressor genes and oncogenes could potentially provide the synergistic overview that could lay the foundations to study telomere‐cancer dynamics at ecosystem levels.

Large-scale diachronic surveys of the composition and dynamics of plant communities in Pyrenean snowbeds - Thomas Masclaux; Gérard Largier; Jocelyne Cambecèdes; Delphine Fallour-Rubio; Elodie Hamdi; Benjamin Komac; Mathieu Menand; Ludovic Olicard; Anne-Sophie Rudi-Dencausse; Laure Sirvent; Estela Illa; Olivier Argagnon; et al. (Plant Ecology, 2022)

Rapid Treatment with Intramuscular Magnesium Sulfate During Cardiopulmonary Resuscitation Does Not Provide Neuroprotection Following Cardiac Arrest - Rui Zhang; Timothy D. Bryson; Garrett M. Fogo; Jinhui Liao; Sarita Raghunayakula; Jennifer Mathieu; Joseph M. Wider; Xiaodan Ren; Kathleen J. Maheras; Katlynn J. Emaus; Erin Gruley; Yuguo Chen; et al. (Molecular Neurobiology, 2022)

Correction to: Toxicogenomics directory of chemically exposed human hepatocytes - Marianna Grinberg; Regina M. Stöber; Karolina Edlund; Eugen Rempel; Patricio Godoy; Raymond Reif; Agata Widera; Katrin Madjar; Wolfgang Schmidt-Heck; Rosemarie Marchan; Agapios Sachinidis; Dimitry Spitkovsky; et al. (Archives of Toxicology, 2022)

Estimating Bycatch From Non-representative Samples (II): A Case Study of Pair Trawlers and Common Dolphins in the Bay of Biscay - Etienne Rouby; Laurent Dubroca; Thomas Cloâtre; Sebastien Demanèche; Mathieu Genu; Kelly Macleod; Hélène Peltier; Vincent Ridoux; Matthieu Authier (Frontiers in Marine Science, 2022)
Marine megafauna plays an important functional role in marine ecosystems as top predators but are threatened by a wide range of anthropogenic activities. Bycatch, the incidental capture of non-targeted species in commercial and recreational fisheries, is of particular concern for small cetacean species, such as dolphins and porpoises. In the North-East Atlantic, common dolphin ( Delphinus delphis , Linné 1758) bycatch has been increasing and associated with large numbers of animals stranding during winter on the French Atlantic seashore since at least 2017. However, uncertainties around the true magnitude of common dolphin bycatch and the fisheries involved have led to delays in the implementation of mitigation measures. Current data collection on dolphin bycatch in France is with non-dedicated observers deployed on vessels for the purpose of national fisheries sampling programmes. These data cannot be assumed representative of the whole fisheries' bycatch events. This feature makes it difficult to use classic ratio estimators since they require a truly randomised sample of the fishery by dedicated observers. We applied a newly developed approach, regularised multilevel regression with post-stratification, to estimate total bycatch from unrepresentative samples and total fishing effort. The latter is needed for post-stratification and the former is analysed in a Bayesian framework with multilevel regression to regularise and better predict bycatch risk. We estimated the number of bycaught dolphins for each week and 10 International Council for the Exploration of the Sea (ICES) divisions from 2004 to 2020 by estimating jointly bycatch risk, haul duration, and the number of hauls per days at sea (DaS). Bycatch risk in pair trawlers flying the French flag was the highest in winter 2017 and 2019 and was associated with the longest haul durations. ICES divisions 8.a and 8.b (shelf part of the Bay of Biscay) were estimated to have the highest common dolphin bycatch. Our results were consistent with independent estimates of common dolphin bycatch from strandings. Our method show cases how non-representative observer data can nevertheless be analysed to estimate fishing duration, bycatch risk and, ultimately, the number of bycaught dolphins. These weekly-estimates improve upon current knowledge of the nature of common dolphin bycatch and can be used to inform management and policy decisions at a finer spatio-temporal scale than has been possible to date. Our results suggest that limiting haul duration, especially in winter, could serve as an effective mitigation strategy.

Kneeling-induced calf ischemia: a pilot study in apparently healthy European young subjects - Pierre Ramondou; Jeanne Hersant; Elise Bernardeau; Thomas Moumneh; Mathieu Feuilloy; Samir Henni; Pierre Abraham (European Journal of Applied Physiology, 2021)

COVID-19 or not COVID-19? Compared characteristics of patients hospitalized for suspected COVID-19 - Thomas Rogier; Isabelle Eberl; Florian Moretto; Thibault Sixt; François-Xavier Catherine; Clémentine Estève; Maroua Abdallahoui; Lucile Behague; Antoine Coussement; Lucas Mathey; Sophie Mahy; Marielle Buisson; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

The future for Mediterranean wetlands: 50 key issues and 50 important conservation research questions - Nigel G. Taylor; Patrick Grillas; Hazem Al Hreisha; Özge Balkız; Maud Borie; Olivier Boutron; Ana Catita; Jocelyn Champagnon; Semia Cherif; Kerim Çiçek; Luís T. Costa; Mohamed Dakki; et al. (Regional Environmental Change, 2021)

Darwin, the devil, and the management of transmissible cancers - Rodrigo Hamede; Thomas Madsen; Hamish McCallum; Andrew Storfer; Paul A. Hohenlohe; Hannah Siddle; Jim Kaufman; Mathieu Giraudeau; Menna Jones; Frédéric Thomas; Beata Ujvari (Conservation Biology, 2021)

European beech stem diameter grows better in mixed than in mono-specific stands at the edge of its distribution in mountain forests - Hans Pretzsch; Torben Hilmers; Enno Uhl; Kamil Bielak; Michal Bosela; Miren del Rio; Laura Dobor; David I. Forrester; Thomas A. Nagel; Maciej Pach; Admir Avdagić; Michal Bellan; et al. (European Journal of Forest Research, 2021)
Recent studies show that several tree species are spreading to higher latitudes and elevations due to climate change. European beech, presently dominating from the colline to the subalpine vegetation belt, is already present in upper montane subalpine forests and has a high potential to further advance to higher elevations in European mountain forests, where the temperature is predicted to further increase in the near future. Although essential for adaptive silviculture, it remains unknown whether the upward shift of beech could be assisted when it is mixed with Norway spruce or silver fir compared with mono-specific stands, as the species interactions under such conditions are hardly known. In this study, we posed the general hypotheses that the growth depending on age of European beech in mountain forests was similar in mono-specific and mixed-species stands and remained stable over time and space in the last two centuries. The scrutiny of these hypotheses was based on increment coring of 1240 dominant beech trees in 45 plots in mono-specific stands of beech and in 46 mixed mountain forests. We found that (i) on average, mean tree diameter increased linearly with age. The age trend was linear in both forest types, but the slope of the age–growth relationship was higher in mono-specific than in mixed mountain forests. (ii) Beech growth in mono-specific stands was stronger reduced with increasing elevation than that in mixed-species stands. (iii) Beech growth in mono-specific stands was on average higher than beech growth in mixed stands. However, at elevations > 1200 m, growth of beech in mixed stands was higher than that in mono-specific stands. Differences in the growth patterns among elevation zones are less pronounced now than in the past, in both mono-specific and mixed stands. As the higher and longer persisting growth rates extend the flexibility of suitable ages or size for tree harvest and removal, the longer-lasting growth may be of special relevance for multi-aged silviculture concepts. On top of their function for structure and habitat improvement, the remaining old trees may grow more in mass and value than assumed so far.

Rheological change and degassing during a trachytic Vulcanian eruption at Kilian Volcano, Chaîne des Puys, France - Mathieu Colombier; Thomas Shea; Alain Burgisser; Timothy H. Druitt; Lucia Gurioli; Dirk Müller; Francisco Cáceres; Kai-Uwe Hess; Pierre Boivin; Didier Miallier; Donald B. Dingwell (Bulletin of Volcanology, 2020)
Magma ascent during silicic dome-forming eruptions is characterized by significant changes in magma viscosity, permeability, and gas overpressure in the conduit. These changes depend on a set of parameters such as ascent rate, outgassing and crystallization efficiency, and magma viscosity, which in turn may influence the prevailing conditions for effusive versus explosive activity. Here, we combine chemical and textural analyses of tephra with viscosity models to provide a better understanding of the effusive-explosive transitions during Vulcanian phases of the 9.4 ka eruption of Kilian Volcano, Chaîne des Puys, France. Our results suggest that effusive activity at the onset of Vulcanian episodes at Kilian Volcano was promoted by (i) rapid ascent of initially crystal-poor and volatile-rich trachytic magma, (ii) a substantial bulk and melt viscosity increase driven by extensive volatile loss and crystallization, and (iii) efficient degassing/outgassing in a crystal-rich magma at shallow depths. Trachytic magma repeatedly replenished the upper conduit, and variations in the amount of decompression and cooling caused vertical textural stratification, leading to variable degrees of crystallization and outgassing. Outgassing promoted effusive dome growth and occurred via gas percolation through large interconnected vesicles, fractures, and tuffisite veins, fostering the formation of cristobalite in the carapace and talus regions. Build-up of overpressure was likely caused by closing of pore space (bubbles and fractures) in the dome through a combination of pore collapse, cristobalite formation, sintering in tuffisite veins, and limited pre-fragmentation coalescence in the dome or underlying hot vesicular magma. Sealing of the carapace may have caused a transition from open- to closed- system degassing and to renewed explosive activity. We generalize our findings to propose that the broad spectrum of eruptive styles for trachytic magmas may be inherited from a combination of characteristics of trachytic melts that include high water solubility and diffusivity, rapid microlite growth, and low melt viscosity compared to their more evolved subalkaline dacitic and rhyolitic equivalents. We show that trachytes may erupt with a similar style (e.g., Vulcanian) but at significantly higher ascent rates than their andesitic, dacitic, and rhyolitic counterparts. This suggests that the periodicity of effusive-explosive transitions at trachytic volcanoes may differ from that observed at the well-monitored andesitic, dacitic, and rhyolitic volcanoes, which has implications for hazard assessment associated with trachytic eruptions.

Paternal morphine self-administration produces object recognition memory deficits in female, but not male offspring - Alexandra S. Ellis; Andre B. Toussaint; Melissa C. Knouse; Arthur S. Thomas; Angela R. Bongiovanni; Hannah L. Mayberry; Shivam Bhakta; Kyle Peer; Debra A. Bangasser; Mathieu E. Wimmer (Psychopharmacology, 2020)

The reuniens and rhomboid nuclei are necessary for contextual fear memory persistence in rats - Etienne Quet; Monique Majchrzak; Brigitte Cosquer; Thomas Morvan; Mathieu Wolff; Jean-Christophe Cassel; Anne Pereira de Vasconcelos; Aline Stéphan (Brain Structure and Function, 2020)

Contrasting resistance and resilience to extreme drought and late spring frost in five major European tree species - Yann Vitasse; Alessandra Bottero; Maxime Cailleret; Christof Bigler; Patrick Fonti; Arthur Gessler; Mathieu Lévesque; Brigitte Rohner; Pascale Weber; Andreas Rigling; Thomas Wohlgemuth (Global Change Biology, 2019)
Extreme climate events (ECEs) such as severe droughts, heat waves, and late spring frosts are rare but exert a paramount role in shaping tree species distributions. The frequency of such ECEs is expected to increase with climate warming, threatening the sustainability of temperate forests. Here, we analyzed 2,844 tree‐ring width series of five dominant European tree species from 104 Swiss sites ranging from 400 to 2,200 m a.s.l. for the period 1930–2016. We found that (a) the broadleaved oak and beech are sensitive to late frosts that strongly reduce current year growth; however, tree growth is highly resilient and fully recovers within 2 years; (b) radial growth of the conifers larch and spruce is strongly and enduringly reduced by spring droughts—these species are the least resistant and resilient to droughts; (c) oak, silver fir, and to a lower extent beech, show higher resistance and resilience to spring droughts and seem therefore better adapted to the future climate. Our results allow a robust comparison of the tree growth responses to drought and spring frost across large climatic gradients and provide striking evidence that the growth of some of the most abundant and economically important European tree species will be increasingly limited by climate warming. These results could serve for supporting species selection to maintain the sustainability of forest ecosystem services under the expected increase in ECEs.

Global mismatches in aboveground and belowground biodiversity - Erin K. Cameron; Inês S. Martins; Patrick Lavelle; Jérôme Mathieu; Leho Tedersoo; Mohammad Bahram; Felix Gottschall; Carlos A. Guerra; Jes Hines; Guillaume Patoine; Julia Siebert; Marten Winter; et al. (Conservation Biology, 2019)
Human activities are accelerating global biodiversity change and have resulted in severely threatened ecosystem services. A large proportion of terrestrial biodiversity is harbored by soil, but soil biodiversity has been omitted from many global biodiversity assessments and conservation actions, and understanding of global patterns of soil biodiversity remains limited. In particular, the extent to which hotspots and coldspots of aboveground and soil biodiversity overlap is not clear. We examined global patterns of these overlaps by mapping indices of aboveground (mammals, birds, amphibians, vascular plants) and soil (bacteria, fungi, macrofauna) biodiversity that we created using previously published data on species richness. Areas of mismatch between aboveground and soil biodiversity covered 27% of Earth's terrestrial surface. The temperate broadleaf and mixed forests biome had the highest proportion of grid cells with high aboveground biodiversity but low soil biodiversity, whereas the boreal and tundra biomes had intermediate soil biodiversity but low aboveground biodiversity. While more data on soil biodiversity are needed, both to cover geographic gaps and to include additional taxa, our results suggest that protecting aboveground biodiversity may not sufficiently reduce threats to soil biodiversity. Given the functional importance of soil biodiversity and the role of soils in human well‐being, soil biodiversity should be considered further in policy agendas and conservation actions by adapting management practices to sustain soil biodiversity and considering soil biodiversity when designing protected areas.

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

From Observation to Information and Users: The Copernicus Marine Service Perspective - Pierre Yves Le Traon; Antonio Reppucci; Enrique Alvarez Fanjul; Lotfi Aouf; Arno Behrens; Maria Belmonte; Abderrahim Bentamy; Laurent Bertino; Vittorio Ernesto Brando; Matilde Brandt Kreiner; Mounir Benkiran; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Homozygous 2p11.2 deletion supports the implication of ELMOD3 in hearing loss and reveals the potential association of CAPG with ASD/ID etiology - Saida Lahbib; Claire S. Leblond; Mariem Hamza; Béatrice Regnault; Laure Lemée; Alexandre Mathieu; Hager Jaouadi; Rahma Mkaouar; Ilhem Ben Youssef-Turki; Ahlem Belhadj; Ichraf Kraoua; Thomas Bourgeron; et al. (Journal of Applied Genetics, 2019)

Distance interaction between marine cave-dwelling sponges and crustaceans - Mathieu Santonja; Stéphane Greff; Marie Le Croller; Olivier P. Thomas; Thierry Pérez (Marine Biology, 2018)

Satellite Radiation Products for Ocean Biology and Biogeochemistry: Needs, State-of-the-Art, Gaps, Development Priorities, and Opportunities - Robert Frouin; Didier Ramon; Emmanuel Boss; Dominique Jolivet; Mathieu Compiègne; Jing Tan; Heather Bouman; Thomas Jackson; Bryan Franz; Trevor Platt; Shubha Sathyendranath (Frontiers in Marine Science, 2018)

Adverse outcome pathways: opportunities, limitations and open questions - Marcel Leist; Ahmed Ghallab; Rabea Graepel; Rosemarie Marchan; Reham Hassan; Susanne Hougaard Bennekou; Alice Limonciel; Mathieu Vinken; Stefan Schildknecht; Tanja Waldmann; Erik Danen; Ben van Ravenzwaay; et al. (Archives of Toxicology, 2017)

Reduction in targeted potentially inappropriate medication use in elderly inpatients: a pragmatic randomized controlled trial - Benoit Cossette; Jean-François Éthier; Thomas Joly-Mischlich; Josée Bergeron; Geneviève Ricard; Serge Brazeau; Mathieu Caron; Olivier Germain; Hélène Payette; Janusz Kaczorowski; Mitchell Levine (European Journal of Clinical Pharmacology, 2017)

Effects of high-altitude exposure on supraspinal fatigue and corticospinal excitability and inhibition - Mathieu Marillier; Pierrick J. Arnal; Thibault Le Roux Mallouf; Thomas Rupp; Guillaume Y. Millet; Samuel Verges (European Journal of Applied Physiology, 2017)

Genomic epidemiology of Cryptococcus yeasts identifies adaptation to environmental niches underpinning infection across an African HIV / AIDS cohort - Mathieu Vanhove; Mathew A. Beale; Johanna Rhodes; Duncan Chanda; Shabir Lakhi; Geoffrey Kwenda; Sile Molloy; Natasha Karunaharan; Neil Stone; Thomas S. Harrison; Tihana Bicanic; Matthew C. Fisher (Molecular Ecology, 2017)
Emerging infections caused by fungi have become a widely recognized global phenomenon and are causing an increasing burden of disease. Genomic techniques are providing new insights into the structure of fungal populations, revealing hitherto undescribed fine‐scale adaptations to environments and hosts that govern their emergence as infections. Cryptococcal meningitis is a neglected tropical disease that is responsible for a large proportion of AIDS ‐related deaths across Africa; however, the ecological determinants that underlie a patient's risk of infection remain largely unexplored. Here, we use genome sequencing and ecological genomics to decipher the evolutionary ecology of the aetiological agents of cryptococcal meningitis, Cryptococcus neoformans and Cryptococcus gattii , across the central African country of Zambia. We show that the occurrence of these two pathogens is differentially associated with biotic (macroecological) and abiotic (physical) factors across two key African ecoregions, Central Miombo woodlands and Zambezi Mopane woodlands. We show that speciation of Cryptococcus has resulted in adaptation to occupy different ecological niches, with C. neoformans found to occupy Zambezi Mopane woodlands and C. gattii primarily recovered from Central Miombo woodlands. Genome sequencing shows that C. neoformans causes 95% of human infections in this region, of which over three‐quarters belonged to the globalized lineage VNI . We show that VNI infections are largely associated with urbanized populations in Zambia. Conversely, the majority of C. neoformans isolates recovered in the environment belong to the genetically diverse African‐endemic lineage VNB , and we show hitherto unmapped levels of genomic diversity within this lineage. Our results reveal the complex evolutionary ecology that underpins the reservoirs of infection for this, and likely other, deadly pathogenic fungi.

Emulator-assisted data assimilation in complex models - Nugzar Yu Margvelashvili; Mike Herzfeld; Farhan Rizwi; Mathieu Mongin; Mark E. Baird; Emlyn Jones; Britta Schaffelke; Edward King; Thomas Schroeder (Ocean Dynamics, 2016)

Design and validation of MEDRYS, a Mediterranean Sea reanalysis over the period 1992–2013 - Mathieu Hamon; Jonathan Beuvier; Samuel Somot; Jean-Michel Lellouche; Eric Greiner; Gabriel Jordà; Marie-Noëlle Bouin; Thomas Arsouze; Karine Béranger; Florence Sevault; Clotilde Dubois; Marie Drevillon; et al. (Ocean Science, 2016)
The French research community in the Mediterranean Sea modeling and the French operational ocean forecasting center Mercator Océan have gathered their skill and expertise in physical oceanography, ocean modeling, atmospheric forcings and data assimilation to carry out a MEDiterranean sea ReanalYsiS (MEDRYS) at high resolution for the period 1992–2013. The ocean model used is NEMOMED12, a Mediterranean configuration of NEMO with a 1∕12° ( ∼ 7 km) horizontal resolution and 75 vertical z levels with partial steps. At the surface, it is forced by a new atmospheric-forcing data set (ALDERA), coming from a dynamical downscaling of the ERA-Interim atmospheric reanalysis by the regional climate model ALADIN-Climate with a 12 km horizontal and 3 h temporal resolutions. This configuration is used to carry a 34-year hindcast simulation over the period 1979–2013 (NM12-FREE), which is the initial state of the reanalysis in October 1992. MEDRYS uses the existing Mercator Océan data assimilation system SAM2 that is based on a reduced-order Kalman filter with a three-dimensional (3-D) multivariate modal decomposition of the forecast error. Altimeter data, satellite sea surface temperature (SST) and temperature and salinity vertical profiles are jointly assimilated. This paper describes the configuration we used to perform MEDRYS. We then validate the skills of the data assimilation system. It is shown that the data assimilation restores a good average temperature and salinity at intermediate layers compared to the hindcast. No particular biases are identified in the bottom layers. However, the reanalysis shows slight positive biases of 0.02 psu and 0.15 °C above 150 m depth. In the validation stage, it is also shown that the assimilation allows one to better reproduce water, heat and salt transports through the Strait of Gibraltar. Finally, the ability of the reanalysis to represent the sea surface high-frequency variability is shown.

Age-specific survival and annual variation in survival of female chamois differ between populations - Josefa Bleu; Ivar Herfindal; Anne Loison; Anne M. G. Kwak; Mathieu Garel; Carole Toïgo; Thomas Rempfler; Flurin Filli; Bernt-Erik Sæther (Oecologia, 2015)

Quantitative determination of sodium monofluoroacetate “1080” in infant formulas and dairy products by isotope dilution LC-MS/MS - Thomas Bessaire; Adrienne Tarres; Alexandre Goyon; Pascal Mottier; Mathieu Dubois; Wan Ping Tan; Thierry Delatour (Food Additives & Contaminants: Part A, 2015)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Genetic and platelet function testing of antiplatelet therapy for percutaneous coronary intervention: the ARCTIC-GENE study - Jean-Philippe Collet; Jean-Sébastien Hulot; Thomas Cuisset; Grégoire Rangé; Guillaume Cayla; Eric Van Belle; Simon Elhadad; Hélène Rousseau; Pierre Sabouret; Stephen A. O’Connor; Jérémie Abtan; Mathieu Kerneis; et al. (European Journal of Clinical Pharmacology, 2015)

miR-375 gene dosage in pancreatic β-cells: implications for regulation of β-cell mass and biomarker development - Mathieu Latreille; Karolin Herrmanns; Neil Renwick; Thomas Tuschl; Maciej T. Malecki; Mark I. McCarthy; Katharine R. Owen; Thomas Rülicke; Markus Stoffel (Journal of Molecular Medicine, 2015)

Microenvironment and phylogenetic diversity of P rochloron inhabiting the surface of crustose didemnid ascidians - Daniel A. Nielsen; Mathieu Pernice; Martin Schliep; Gaurav Sablok; Thomas C. Jeffries; Michael Kühl; Daniel Wangpraseurt; Peter J. Ralph; Anthony W. D. Larkum (Environmental Microbiology, 2015)
Summary The cyanobacterium P rochloron didemni is primarily found in symbiotic relationships with various marine hosts such as ascidians and sponges. P rochloron remains to be successfully cultivated outside of its host, which reflects a lack of knowledge of its unique ecophysiological requirements. We investigated the microenvironment and diversity of P rochloron inhabiting the upper, exposed surface of didemnid ascidians, providing the first insights into this microhabitat. The pH and O 2 concentration in this P rochloron biofilm changes dynamically with irradiance, where photosynthetic activity measurements showed low light adaptation (E k ∼80 ± 7 μmol photons m −2 s −1 ) but high light tolerance. Surface P rochloron cells exhibited a different fine structure to P rochloron cells from cloacal cavities in other ascidians, the principle difference being a central area of many vacuoles dissected by single thylakoids in the surface P rochloron . Cyanobacterial 16S rDNA pyro‐sequencing of the biofilm community on four ascidians resulted in 433 operational taxonomic units ( OTUs ) where on average −85% (65–99%) of all sequence reads, represented by 136 OTUs , were identified as P rochloron via blast search. All of the major P rochloron ‐ OTUs clustered into independent, highly supported phylotypes separate from sequences reported for internal P rochloron , suggesting a hitherto unexplored genetic variability among P rochloron colonizing the outer surface of didemnids.

Levels and limits in artificial selection of communities - Manuel Blouin; Battle Karimi; Jérôme Mathieu; Thomas Z. Lerch (Ecology Letters, 2015)
Artificial selection of individuals has been determinant in the elaboration of the Darwinian theory of natural selection. Nowadays, artificial selection of ecosystems has proven its efficiency and could contribute to a theory of natural selection at several organisation levels. Here, we were not interested in identifying mechanisms of adaptation to selection, but in establishing the proof of principle that a specific structure of interaction network emerges under ecosystem artificial selection. We also investigated the limits in ecosystem artificial selection to evaluate its potential in terms of managing ecosystem function. By artificially selecting microbial communities for low CO 2 emissions over 21 generations ( n = 7560), we found a very high heritability of community phenotype (52%). Artificial selection was responsible for simpler interaction networks with lower interaction richness. Phenotype variance and heritability both decreased across generations, suggesting that selection was more likely limited by sampling effects than by stochastic ecosystem dynamics.

Diversifying mechanisms in the on‐farm evolution of crop mixtures - Mathieu Thomas; Stéphanie Thépot; Nathalie Galic; Sophie Jouanne‐Pin; Carine Remoué; Isabelle Goldringer (Molecular Ecology, 2015)
While modern agriculture relies on genetic homogeneity, diversifying practices associated with seed exchange and seed recycling may allow crops to adapt to their environment. This socio‐genetic model is an original experimental evolution design referred to as on‐farm dynamic management of crop diversity. Investigating such model can help in understanding how evolutionary mechanisms shape crop diversity submitted to diverse agro‐environments. We studied a French farmer‐led initiative where a mixture of four wheat landraces called ‘Mélange de Touselles’ (MDT) was created and circulated within a farmers' network. The 15 sampled MDT subpopulations were simultaneously submitted to diverse environments (e.g. altitude, rainfall) and diverse farmers' practices (e.g. field size, sowing and harvesting date). Twenty‐one space‐time samples of 80 individuals each were genotyped using 17 microsatellite markers and characterized for their heading date in a ‘common‐garden’ experiment. Gene polymorphism was studied using four markers located in earliness genes. An original network‐based approach was developed to depict the particular and complex genetic structure of the landraces composing the mixture. Rapid differentiation among populations within the mixture was detected, larger at the phenotypic and gene levels than at the neutral genetic level, indicating potential divergent selection. We identified two interacting selection processes: variation in the mixture component frequencies, and evolution of within‐variety diversity, that shaped the standing variability available within the mixture. These results confirmed that diversifying practices and environments maintain genetic diversity and allow for crop evolution in the context of global change. Including concrete measurements of farmers' practices is critical to disentangle crop evolution processes.

Pathogenesis of adult-onset Still’s disease: new insights from the juvenile counterpart - Yvan Jamilloux; Mathieu Gerfaud-Valentin; Fabio Martinon; Alexandre Belot; Thomas Henry; Pascal Sève (Immunologic Research, 2015)

Toxicogenomics directory of chemically exposed human hepatocytes - Marianna Grinberg; Regina M. Stöber; Karolina Edlund; Eugen Rempel; Patricio Godoy; Raymond Reif; Agata Widera; Katrin Madjar; Wolfgang Schmidt-Heck; Rosemarie Marchan; Agapios Sachinidis; Dimitry Spitkovsky; et al. (Archives of Toxicology, 2014)

LC-MS/MS analytical procedure to quantify tris (nonylphenyl)phosphite, as a source of the endocrine disruptors 4-nonylphenols, in food packaging materials - Pascal Mottier; Nancy Frank; Mathieu Dubois; Adrienne Tarres; Thomas Bessaire; Roman Romero; Thierry Delatour (Food Additives & Contaminants: Part A, 2014)

Detailed multidisciplinary monitoring reveals pre- and co-eruptive signals at Nyamulagira volcano (North Kivu, Democratic Republic of Congo) - Benoît Smets; Nicolas d’Oreye; François Kervyn; Matthieu Kervyn; Fabien Albino; Santiago R. Arellano; Montfort Bagalwa; Charles Balagizi; Simon A. Carn; Thomas H. Darrah; José Fernández; Bo Galle; et al. (Bulletin of Volcanology, 2014)

Chronic ingestion of cadmium and lead alters the bioavailability of essential and heavy metals, gene expression pathways and genotoxicity in mouse intestine - Jérôme Breton; Kelly Le Clère; Catherine Daniel; Mathieu Sauty; Lauren Nakab; Thierry Chassat; Joëlle Dewulf; Sylvie Penet; Christophe Carnoy; Patrick Thomas; Bruno Pot; Fabrice Nesslany; et al. (Archives of Toxicology, 2013)

Climate variability and trends in downscaled high-resolution simulations and projections over Metropolitan France - Robert Vautard; Thomas Noël; Laurent Li; Mathieu Vrac; Eric Martin; Philippe Dandin; Julien Cattiaux; Sylvie Joussaume (Climate Dynamics, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Range expansion in an invasive small mammal: influence of life-history and habitat quality - Thomas A. White; Mathieu G. Lundy; W. Ian Montgomery; Sally Montgomery; Sarah E. Perkins; Colin Lawton; John M. Meehan; Tom J. Hayden; Gerald Heckel; Neil Reid; Jeremy B. Searle (Biological Invasions, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Right Hemisphere Recruitment During Language Processing in Frontotemporal Lobar Degeneration and Alzheimer’s Disease - Natalie Nelissen; Patrick Dupont; Mathieu Vandenbulcke; Thomas Tousseyn; Ronald Peeters; Rik Vandenberghe (Journal of Molecular Neuroscience, 2011)

Alternative (non-animal) methods for cosmetics testing: current status and future prospects—2010 - Sarah Adler; David Basketter; Stuart Creton; Olavi Pelkonen; Jan van Benthem; Valérie Zuang; Klaus Ejner Andersen; Alexandre Angers-Loustau; Aynur Aptula; Anna Bal-Price; Emilio Benfenati; Ulrike Bernauer; et al. (Archives of Toxicology, 2011)

Seed exchanges, a key to analyze crop diversity dynamics in farmer-led on-farm conservation - Mathieu Thomas; Julie C. Dawson; Isabelle Goldringer; Christophe Bonneuil (Genetic Resources and Crop Evolution, 2011)

Gaudeamus lavocati sp. nov. (Rodentia, Hystricognathi) from the early Oligocene of Zallah, Libya: first African caviomorph? - Pauline Coster; Mouloud Benammi; Vincent Lazzari; Guillaume Billet; Thomas Martin; Mustafa Salem; Awad Abolhassan Bilal; Yaowalak Chaimanee; Mathieu Schuster; Xavier Valentin; Michel Brunet; Jean-Jacques Jaeger (The Science of Nature, 2010)

Analyses of associations with asthma in four asthma population samples from Canada and Australia - Denise Daley; Mathieu Lemire; Loubna Akhabir; Moira Chan-Yeung; Jian Qing He; Treena McDonald; Andrew Sandford; Dorota Stefanowicz; Ben Tripp; David Zamar; Yohan Bosse; Vincent Ferretti; et al. (Human Genetics, 2009)

Optimal first feed organism for South African mud crab Scylla serrata (Forskl) larvae - Jerome A. Davis; Mathieu Wille; Thomas Hecht; Patrick Sorgeloos (Aquaculture International, 2005)

End-member ferrian kanonaite: an andalusite phase with one Al fully replaced by (Mn, Fe) 3+ in a quartz vein from the Ardennes mountains, Belgium, and its origin - Werner Schreyer; Heinz-Jrgen Bernhardt; Andr-Mathieu Fransolet; Thomas Armbruster (Contributions to Mineralogy and Petrology, 2004)

Genetic differentiation of Niphargus rhenorhodanensis(Amphipoda) from interstitial and karst environments - Jacques Mathieu; Fabrice Jeannerod; Frédéric Hervant; Thomas C. Kane (Aquatic Sciences, 1997)

Genetic differentiation ofNiphargus rhenorhodanensis (Amphipoda) from interstitial and karst environments - Jacques Mathieu; Fabrice Jeannerod; Frédéric Hervant; Thomas C. Kane (Aquatic Sciences, 1997)